2020
DOI: 10.1080/19475411.2020.1783020
|View full text |Cite
|
Sign up to set email alerts
|

The square rod-shaped ionic polymer-metal composite and its application in interventional surgical guide device

Abstract: Ionic polymer-metal composite (IPMC) is an electro-active polymer material, which has many advantages such as small size, light weight, low driving voltage, large strain, and good biocompatibility. However, the conventional sheet IPMC has the shortcoming of only bending in the two-dimensional plane, which greatly limits the application of IPMC in the field of interventional surgery. In this work, a square rodshaped IPMC with multi-degree-of-freedom motion was fabricated, and the displacement and blocking force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
17
2
Order By: Relevance
“…It can be seen from Figure 4e and Figure 4f that there are folds on the electrode surfaces of the printed IPMCs. This is a common phenomenon, which was described in references [11] and [13], and the IPMC prepared using commercial membrane or cast membrane also has such folds. The electrode layer of the printed IPMC also has the groove structure, as shown in Figure 4g.…”
Section: Morphology Observationsmentioning
confidence: 76%
See 1 more Smart Citation
“…It can be seen from Figure 4e and Figure 4f that there are folds on the electrode surfaces of the printed IPMCs. This is a common phenomenon, which was described in references [11] and [13], and the IPMC prepared using commercial membrane or cast membrane also has such folds. The electrode layer of the printed IPMC also has the groove structure, as shown in Figure 4g.…”
Section: Morphology Observationsmentioning
confidence: 76%
“…In order to drive the IPMCs, the nanogenerator must have a voltage of 1~10 V and power of several watts [11][12][13]. IPMCs are widely used in medical and bionic robot fields, including medical catheters [11,[14][15][16], surgical microforceps [12], heartcompression devices [17], underwater robots and biomimetic fish [18,19], driving of imitation gecko toes [20], and flapping devices of bionic insects [13]. IPMCs are traditionally fabricated by electroless plating based on the commercial recast membrane, which has some shortcomings such as a long fabrication period, a tedious process, a single shape and an uncontrollable thickness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the engineering applications, IPMCs have also been proposed for medical devices or biomedical applications because of their unique stimulus-response actuation performance. [134][135][136][137][138] Guo et al proposed the application of an ionic actuator as a guide for microcatheter with two degrees of freedom in the front section as servo actuators, and the results showed that IPMC was applicable to intracavity operations. [139] Lu et al prepared a MDOF IPMC active catheter by an electrode splitting technique, aiming to obtain the deformation capability in 3D space.…”
Section: Medical Devicesmentioning
confidence: 99%
“…Therefore, from a comprehensive point of view, the current IPMCs have great application prospects in the field of underwater bionic robots to realize underwater environmental investigation, water quality monitoring, or underwater cultural relic salvage. Furthermore, IPMCs can also be used as a guide device [196] for interventional catheters [192] in human vascular interventional operations, where traditional surgical catheters are difficult to operate and cannot be actively guided. IPMCs are beneficial, because they take advantage of liquid environments, such as underwater environments or human blood vessels.…”
Section: Medical Engineeringmentioning
confidence: 99%